DNA methylation profiles in individuals with rare, atypical 7q11.23 CNVs correlate with GTF2I and GTF2IRD1 copy number - Strong, Emma; Mervis, Carolyn B.; Tam, Elaine; Morris, Colleen A.; Klein-Tasman, Bonita P.; Velleman, Shelley L.; Osborne, Lucy R. (Npj genomic medicine, 2023)
Williams-Beuren syndrome (WBS) and 7q11.23 duplication syndrome (Dup7) are rare neurodevelopmental disorders caused by deletion and duplication of a 1.5 Mb region that includes at least five genes with a known role in epigenetic regulation. We have shown that CNV of this chromosome segment causes dose-dependent, genome-wide changes in DNA methylation, but the specific genes driving these changes are unknown. We measured genome-wide whole blood DNA methylation in six participants with atypical CNV of 7q11.23 (three with deletions and three with duplications) using the Illumina HumanMethylation450k array and compared their profiles with those from groups of individuals with classic WBS or classic Dup7 and with typically developing (TD) controls. Across the top 1000 most variable positions we found that only the atypical rearrangements that changed the copy number of GTF2IRD1 and/or GTF2I (coding for the TFII-IRD1 and TFII-I proteins) clustered with their respective syndromic cohorts. This finding was supported by results from hierarchical clustering across a selection of differentially methylated CpGs, in addition to pyrosequencing validation. These findings suggest that CNV of the GTF2I genes at the telomeric end of the 7q11.23 interval is a key contributor to the large changes in DNA methylation that are seen in blood DNA from our WBS and Dup7 cohorts, compared to TD controls. Our findings suggest that members of the TFII-I protein family are involved in epigenetic processes that alter DNA methylation on a genome-wide level.